Influence of railway transport in the South-East of Slovakia on formation of adventive flora in Central Europe - Jehlík, Vladimír; Dostálek, Jiří (Biodiversity: Research and Conservation, 2008)
The contribution features data on the occurrence of plants introduced mostly by the year 1979 via grain railway transports from the territory of former USSR (mostly south of Ukraine, South-East of the European part of Russia, Central Asia) to the areas of 3 selected railway transhipment stations (Čierna nad Tisou and its wider vicinity) in the “Východoslovenská nížina” (East-Slovakian Plain), in the Slovak Republic. On these localities, approximately 500 species of vascular plants are present, of which around one third is recognized as phytogeographically important (in total, 144 taxa). This new reservoir of diasporas of eastern synanthropic plant species can have a significant impact on the present diversity of Slovak flora as well as flora of neighbouring countries. Almost half of those 144 species, listed in the contribution, have more or less continental distribution. In majority it concerns thermophilous steppe and forest-steppe to semi-desert species (the latter ones only very rarely) of southern territories, which is correlated of the South-East of Slovakia. Moreover, for the first time, two following species, introduced into the transhipment station in Čierna nad Tisou from the East, are published for the flora of Slovakia: Artemisia dniproica Klokov and Centaurea adpressa (Ledeb.) Prodan. Apart from continental species, also Mediterranean species s.l. are frequently present. In addition, the number of North American species is relatively high. They were spreading in a westerly direction, probably from the East, where they have already become occasionally naturalised. All these species gradually enrich the eastern migration route of adventive plants in Central Europe.